PENGARUH PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Rinawati, Rinawati; Abdurrahman, Abdurrahman; Jalmo, Tri (FKIP Universitas Lampung, 2016)
The Effects of Problem Based Learning on Critical Thinking Skills Students. This study aimed to determine the effect of Problem Based Learning model in improving students’ critical thinking skills. Samples were VIIA and VIIC grade students of SMPN 22 Bandar Lampung selected by purposive sampling. The research design was pretest-posttest not equivalent. The quantitative data were in the form of students’ critical thinking skills measured by written test obtained from the pretest and posttest and analyzed using t test with significance level of 5%. Learning activity data were analyzed descriptively. The results showed that N-gain of experimental class students (0.77) and differed significantly higher than the control group (0.57). Activities of students in the experimental class (83,25%) higher than the control class (66,04%). It can be concluded that Problem Based Learning model can improve critical thinking skills and student learning activities. Keywords: problem based learning, critical thinking skills, learning activity DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601